Pengaruh Top Management Support dan Budaya Organisasi Terhadap Sistem Informasi Akuntansi dengan Inovasi Sebagai Variabel Moderasi - Al Biruni, Raga Taqwa; Bastian, Elvin (Innovative: Journal Of Social Science Research, 2024)
With innovation acting as a moderating variable, the objective of this research is to ascertain how organizational culture and top management support affect accounting information systems (empirical study on hotel enterprises in Serang City and Cilegon City). This study focuses on quantitative research. The populace uses hotels in Cilegon City and Serang City. This study employed purposive sampling, and the six hotel chains that satisfied the criteria were chosen to comprise the research sample. The questionnaire that provided the core data for this study. The analytical approach used in this study is structural equation modeling using PLS using SmartPLS version 3 software. The study's findings demonstrate that organizational culture has a favorable impact on the Accounting Information System and that top management support.